Yield Performance of Okra (Abelmoschus esculentus L. Moench) and Maize (Zea mays L.) as Affected by Time of Planting Maize in Makurdi, Nigeria. (27th June 2012) - Ijoyah, M. O.; Dzer, D. M.
Abstract : Field experiments were conducted from June to October during 2010 and 2011 cropping seasons at the Research Farm, University of Agriculture, Makurdi, Nigeria, to evaluate the yield performance of okra-maize mixture as affected by time of planting maize. The experiment consisted of three maize planting dates (maize planted at the same time as okra in mid-June, maize planted 2 and 4 weeks later, respectively, in late June and early July) to okra plots. Monocropped okra and maize constituted the control plots. The five treatments were replicated four times in a randomized complete block design. The results obtained showed that the greatest intercrop yield of okra was obtained when maize was planted 4 weeks later (in early July), while the greatest intercrop yield of maize was produced when planted at the same time as okra in mid-June. Planting okra and maize at the same time in mid-June not only recorded the lowest competitive pressure, but also gave the highest land equivalent ratio (LER) values of 1.78 and 1.75, respectively, in years 2010 and 2011, indicating that greater productivity per unit area was achieved by growing the two crops together than by growing them separately. With these LER values, 43.8% and 42.9% of land were saved, respectively, in 2010 and 2011. Both crops were found most suitable in mixture when planting was done at the same time in mid-June. This should be recommended for Makurdi location, Nigeria.